Pengaruh Pembelajaran Pendidikan Agama Islam Terhadap Akhlak Peserta Didik Kelas VIII di SMP Negeri 3 Lembang Kabupaten Pinrang - Nurhudayana; Muh. Djunaidi; Buhaerah (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
The results of this study indicate that Islamic Education is influence of Islamic Religious Education Learning on the morals of grade VIII students in Junior High School 3 Lembang, Pinrang Regency. This can be proven by analyzing data from the results of the questionnaire chosen by respondents and based on the simple linear regression test showing that the value of Y = 20,115 + 0,647 X from the results of the simple linear regression test that the level of Islamic religious education is directly proportional to the morals of students and the hypothesis test the correlation test shows that the value of R2 = 0, 576 or 0.576 x 100% = 57.6% and in the Sig test tcount against H1 shows tilapia = 8.316 ˃ table 2.006 thus H1 is accepted and H0 is rejected, thus conclusions can be drawn that Islamic Education influences the morals of students in class VIII at SMP Negeri 3 Lembang Pinrang Regency and the contribution given is 57.6%.